1998
DOI: 10.1128/aem.64.8.2925-2930.1998
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Anaerobic Phosphate Release by Nitric Oxide in Activated Sludge

Abstract: Activated sludge not containing significant numbers of denitrifying, polyphosphate [poly(P)]-accumulating bacteria was grown in a fill-and-draw system and exposed to alternating anaerobic and aerobic periods. During the aerobic period, poly(P) accumulated up to 100 mg of P · g of (dry) weight. When portions of the sludge were incubated anaerobically in the presence of acetate, 80 to 90% of the intracellular poly(P) was degraded and released as orthophosphate. Degradation of poly(P) was mainly catalyzed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The presence of nitrate is thought to provide denitrifying bacteria with an opportunity to remove the selective advantage the PAO have in these systems by out-competing them for the metabolizable substrates available there [159^163]. However, the inhibitory e¡ect of nitrate may be more direct because nitric oxide, an intermediate in denitri¢cation has been shown to prevent anaerobic P release in EBPR sludge by inhibiting the adenylate kinase (see Section 14) involved in polyP degradation [164].…”
Section: Denitrifying Ebpr Systemsmentioning
confidence: 99%
“…The presence of nitrate is thought to provide denitrifying bacteria with an opportunity to remove the selective advantage the PAO have in these systems by out-competing them for the metabolizable substrates available there [159^163]. However, the inhibitory e¡ect of nitrate may be more direct because nitric oxide, an intermediate in denitri¢cation has been shown to prevent anaerobic P release in EBPR sludge by inhibiting the adenylate kinase (see Section 14) involved in polyP degradation [164].…”
Section: Denitrifying Ebpr Systemsmentioning
confidence: 99%
“…The assumption that PAOs are less capable of nitrate reduction also led to the exclusion of denitrification from early EBPR models Wentzel, Ekama, Loewenthal, Dold, and Marais, 1989). Poor phosphorus removal under nitrate-rich conditions in the anaerobic zone has been attributed to the disruption of anaerobic conditions by nitrate (Barnard, 1976), consumption of fatty acids by denitrifying non-polyphosphate heterotrophs (Barker and Dold, 1996;Hascoet and Florentz, 1985b), and inhibition of PAOs by nitrite, as a result of incomplete denitrification (Ahn et al, 2001;Hu et al, 2003;Jiang et al, 2006;Meinhold, Arnold, and Isaacs, 1999;Saito et al, 2004;van Niel et al, 1998;Zhou et al, 2007).…”
Section: Polyphosphate-accumulating Organismsmentioning
confidence: 99%
“…Another aspect worthy of mentioning is that, despite the presence of nitrate at the beginning of most batch testing (ranging from 8.1 to 15 mg/L), P release occurred simultaneously without any delays (Supporting Information Figure ). Several studies have shown that nitrate has a negative effect on the EBPR performance during the anaerobic phase, due to the competition for carbon between the denitrifying population and the PAOs (López‐Vázquez et al, ; Yagci, Artan, Çokgör, Randall, & Orhon, ), and possible inhibitory effect of nitric oxide produced during denitrification (Van Niel, Appeldoorn, Zehnder, & Kortstee, ). The results of this study showed that the presence of nitrate did not seem to significantly affect the P release rate.…”
Section: Resultsmentioning
confidence: 99%